n Studie van die meganisme van werking van 2,4-D en mcpa in Raphanus Raphanistrum L - Van Rensburg, A. J. Janse (Stellenbosch : Stellenbosch University, 2012)
Dissertation (MScAgric) -- University of Stellenbosch, 1974.